Overview of performances and service behaviors of uranyl nitrate solution for medical aqueous homogeneous reactors. (March 2023) - Duan, Zhengang; Zhao, Yanli; Lv, Liangliang; Li, Wenjie; Li, Yuanming; Jiao, Yongjun; Xin, Yong; Lei, Tao; Peng, Yuan
Abstract: The growing human demand for better health and the under-supply of medical isotope in the international market bring unprecedented developing opportunities for medical isotope technology, and also promo te the rapid development of aqueous homogeneous reactor (AHR) technology, especially for the production of medical isotopes. As the technology core of AHR, the design and service behaviors of the fuel solution are a matter of the safety and economy of AHR. Uranyl nitrate (UO2 (NO3 )2 ) is one of the candidate nuclear fuels for AHR, so its properties and performances are necessary for fuel design and operation analysis. In this manuscript, an attempt has been made to systematically review the key properties of UO2 (NO3 )2 solution including the thermal stability, solubility, density, viscosity, freezing point, boiling point, acidity, specific heat capacity, surface tension and thermal conductivity, as well as the factors affecting these properties. Subsequently, the irradiation behaviors, chemical precipitation behaviors of UO2 (NO3 )2 solution, and corrosion behaviors of contact materials have been introduced. The shortcomings of the present research are pointed out and some suggestions are made on the design of uranium concentration, operating temperature, the cycle of isotope extraction and solution purification. Highlights: The key properties and influencing factors of UO2 (NO3 )2 solution are systematically reviewed. The key service behaviors of UO2 (NO3 )2 solution have been introduced. Some suggestions are made on the design of UO2 (NO3 )2 solution for AHRs.